(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The results of researches on the Macrolepidoptera collected in the WWF Nature Reserve "Guardiaregia-Campochiaro" (Molise Region, Italy) were reported. A total of 299 species were caught, 29 of which found for the first time in Molise. For Philereme vetulata (Denis & Schiffermiiller, 1775), Chersotis cuprea (Denis & Schiffermiiller, 1775) and Eilema pseudocomplana (Daniel, 1939) it was the southermost finding in Italy. The diversity and richness of the Macrolepidoptera fauna was evaluated, using diversity indices (Fisher’ alpha, Shannon and Simpson), similarity index (Sørensen) and species richness indices (ACE and ICE). Results showed a decline in biodiversity and species richness with increasing altitude and a low similarity among sites. The work contributed to the faunistical knowledge of Apennine and underlined the method effectiveness and the usefulness of such as indices in environmental evaluations.